Cervical artery dissection in young adults in the stroke in young fabry patients (sifap1) study - Sarnowski, Bettina von; Hennerici, Michael G. (Cerebrovascular diseases, 2015)
Background: Patients with carotid artery dissection (CAD) have been reported to have different vascular risk factor profiles and clinical outcomes to those with vertebral artery dissection (VAD). However, there are limited data from recent, large international studies comparing risk factors and clinical features in patients with cervical artery dissection (CeAD) with other TIA or ischemic stroke (IS) patients of similar age and sex. Methods: We analysed demographic, clinical and risk factor profiles in TIA and IS patients ≤55 years of age with and without CeAD in the large European, multi-centre, Stroke In young FAbry Patients 1 (sifap1) study. Patients were further categorised according to age (younger: 18-44 years; middle-aged: 45-55 years), sex, and site of dissection. Results: Data on the presence of dissection were available in 4,208 TIA and IS patients of whom 439 (10.4%) had CeAD: 196 (50.1%) had CAD, 195 (49.9%) had VAD, and 48 had multiple artery dissections or no information regarding the dissected artery. The prevalence of CAD was higher in women than in men (5.9 vs. 3.8%, p < 0.01), whereas the prevalence of VAD was similar in women and men (4.6 vs. 4.7%, n.s.). Patients with VAD were younger than patients with CAD (median = 41 years (IQR = 35-47 years) versus median = 45 years (IQR = 39-49 years); p < 0.01). At stroke onset, about twice as many patients with either CAD (54.0 vs. 23.1%, p < 0.001) or VAD (63.4 vs. 36.6%, p < 0.001) had headache than patients without CeAD and stroke in the anterior or posterior circulation, respectively. Compared to patients without CeAD, hypertension, concomitant cardiovascular diseases and a patent foramen ovale were significantly less prevalent in both CAD and VAD patients, whereas tobacco smoking, physical inactivity, obesity and a family history of cerebrovascular diseases were found less frequently in CAD patients, but not in VAD patients. A history of migraine was observed at a similar frequency in patients with CAD (31%), VAD (27.8%) and in those without CeAD (25.8%). Conclusions: We identified clinical features and risk factor profiles that are specific to young patients with CeAD, and to subgroups with either CAD or VAD compared to patients without CeAD. Therefore, our data support the concept that certain vascular risk factors differentially affect the risk of CAD and VAD.